Prosedur Pemeriksaan MRI Lumbal pada Kasus Efusi Pleura Suspek Tuberkulosis - Fani Susanto; Arga Pratama Rahardian; Hernastiti Sedya Utami; Widya Mufida (Poltekkes Kemenkes Semarang, 2023)
Background: Clinical vertebral tuberculosis (TB) occurs outside the lungs affecting the spine. It generally infects the spine in the lower thoracic and upper lumbar spine. MRI examination is performed on clinical vertebral TB patients to determine the degree of stress and changes in bone elements in the early stages of the disease. This study aims to analyze the lumbar MRI examination procedure in cases of suspected TB pleural effusion. Methods: This research was qualitative with a case study approach. Data collection was carried out at the Radiology Unit of Premier Bintaro Hospital with the methods of observation, interviews, and documentation. Data processing and analysis were carried out descriptively. Results: Lumbar MRI examination with suspected TB pleural effusion at the Radiology Unit of Premier Bintaro Hospital was not specially prepared, the patient was examined first through the patient checklist to avoid metal materials entering the examination room. Examination using the Non-Contrast Lumbar MRI protocol included of sagittal and coronal T2, sagittal T1, sagittal Short Tau Inverse Recovery (STIR), Myelography, Axial T2, and Axial T1. The results of the examination provided sufficient diagnostic information to indicate a vertebral TB lesion. Conclusions: The procedure for examining lumbar MRI in TB cases with suspected pleural effusion at the Radiology Unit of Premier Bintaro Hospital did not require special preparation, the examination protocol used was to provide TB clinical diagnostic information, the addition of Gadolinium contrast media could be an alternative choice.